Synthesis of Modified Phase-Changing Material with Latent Heat and Thermal Conductivity to Store Solar Energy Using a Carbon Nanotube - V. Vedanarayanan; J. Dilli Srinivasan; K. Arulvendhan; P. Thirusenthil Kumaran; R. Selvakumar; H. S. Asif; M. H. Siddique; Jifara Chimdi (International Journal of Photoenergy)
MicroPCMs’ excellent thermal capacity and photothermal translation features benefit solar energy storage applications significantly. A successful in situ polymerization procedure was employed to build microencapsulated phase-change materials using n-hexadecanol as the core and melamine-formaldehyde resin as the outer shell, and the thermal characteristics of the microPCMs were evaluated. In terms of micromorphology, the incorporation of hydroxylated carbon nanotubes into microPCMs with a compact shell has little effect on their spherical structure. MicroPCMs’ melting heat and latent heat are both 51.5°C with a 0.2 weight percent dose of hydroxylated carbon nanotubes, and n-energy hexadecanol’s storage efficiency is determined to be 75.25 percent. Thermal conductivity and photothermal conversion efficiency of microencapsulated phase-change materials engendered with increased hydroxylated carbon nanotube dosage have improved significantly, laying the foundation for improved photothermal storage efficiency. When 0.6 weight % hydroxylated carbon nanotubes are added to the mixture, microencapsulated phase-change materials have a thermal conduction of 0.3597 Wm−1·K−1 and 181.5 J·g−1. Additionally, all of the improved microPCMs show exceptional thermal stability across 500 heat cycles. Because of their large thermal capability and efficient photothermal conversion, the new microPCMs appear to be an appealing option for solar energy storage in direct-absorption solar collector systems.